2021
DOI: 10.21037/tau-21-112
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of postoperative ileus following laparoscopic radical cystectomy and developing a points-based risk assessment scale

Abstract: Background: Postoperative ileus (POI) is one of the most common complications after laparoscopic radical cystectomy (LRC). Albeit its high incidence, its risk factors are obscure, and few studies have attempted to explore them. Meanwhile, risk-assessing tools for predicting its happening are lacking. Methods: Clinical data of 197 patients who underwent LRC between March 2014 and October 2019 were retrospectively collected. All cases of POI were identified and double-checked. Data pertaining to the following ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…constipation and increased dosage of laxatives (7). POI is the most common cause of prolonged LOS after RC (8).…”
Section: Identification Of Risk Factors and Clinical Model Constructi...mentioning
confidence: 99%
See 1 more Smart Citation
“…constipation and increased dosage of laxatives (7). POI is the most common cause of prolonged LOS after RC (8).…”
Section: Identification Of Risk Factors and Clinical Model Constructi...mentioning
confidence: 99%
“…Increased intravenous fluids is associated with prolonged POI and longer LOS in patients who underwent robot-assisted radical cystectomy (RARC) ( 6 ). Xue et al reported that factors for ileus post-cystectomy include chronic constipation and increased dosage of laxatives ( 7 ). POI is the most common cause of prolonged LOS after RC ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Increased intravenous uids are associated with prolonged POI and longer length of LOS in patients who underwent robot-assisted radical cystectomy (RARC) 6 . Xue et al reported that factors for ileus post-cystectomy include chronic constipation and increased dosage of laxatives 7 . POI is the most common cause of prolonged LOS after RC 8 .…”
Section: Introductionmentioning
confidence: 99%